Hukuman Mati dalam Pasal 340 KUHP dan Hadits Riwayat Muslim Nomor 1676 - Ardiansyah, Ardiansyah; Arifin, Tajul (INDO PUBLISHING, 2025)
The death penalty is the most severe law in the Indonesian legal system. This law is applied to provide a deterrent effect, even so the death penalty often causes this because it is considered contrary to Human Rights (HAM). In Islamic law there is also a law of qisas which uses the concept of the death penalty as a form of appropriate retaliation for the crime of murder. This paper aims to analyze the relevance between the provisions of the death penalty in Article 340 of the Criminal Code and the concept of qisas in Islamic law. This study uses a normative juridical approach with a descriptive-analytical method through literature studies. The results of the study indicate that there is a meeting point in the value of justice between the death penalty in Indonesian positive law and the principle of qisas in Islamic law, both of which aim to maintain the right to life and social peace.